# This is geeky, but the conclusion is universal appreciable, I feel.

Posted by on August 8, 2007

I think this is cool.
[note: all calculations have been performed by the author using gross simplifications. DO NOT EAT.]

In a closed system, energy is conserved, which means that if you start out with no kinetic energy, and wind up with kinetic energy by using up potential energy only, your final kinetic energy equals your initial kinetic energy, or symbolically:

{KE(final)-KE(initial)}+{PE(final)-PE(initial)} = 0

{KE(final)-KE(initial)} = -{PE(final)-PE(initial)}

{KE(final)-KE(initial)} = {PE(initial)-PE(final)}

If KE(inital) = 0 and PE(final) = 0 then

KE(final)=PE(initial)

next step.

KE = (1/2)mv^2 where m is mass and v is velocity

PE = mgh where m is mass, g is acceleration due to gravity and h is height

so we have

mgh = (1/2)mv^2

cancelling m’s and multiplying by 2 we get

2gh=v^2

Using the equation above, and discounting wind resistance of any kind(not really possible in my scenario) also discounting friction of any kind(I imagine a slip ‘n’ slide running the entire length of the beast.) we get:

If I start from rest at the top of mount everest and sit on a Slip ‘n’ Slide, by the time I reach the bottom, I will be traveling 931 miles per hour. I want to do this.